2016
DOI: 10.1080/07481187.2016.1186761
|View full text |Cite
|
Sign up to set email alerts
|

Blurred world view: A study on the relationship between television viewing and the perception of the justice system

Abstract: Previous studies suggest that distorted representations of reality on television can lead to distorted perceptions of reality among viewers. In this study, 322 individuals in Austria reported their weekly television consumption and whether they believe that there is active practice of capital punishment in Austria, which has been abolished since 1968. The more television participants watched, the more likely they mistakenly believed that there is, or recently was, capital punishment in Austria, even when contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
64
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(71 citation statements)
references
References 38 publications
4
64
3
Order By: Relevance
“…Till et al (2016) reported that in an Austrian sample approximately one in ten respondents incorrectly believed that Austria still practices, or recently practiced, the death penalty, and that there is a positive association between the amount of weekly television viewing and this gross misperception of the Austrian justice system.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Till et al (2016) reported that in an Austrian sample approximately one in ten respondents incorrectly believed that Austria still practices, or recently practiced, the death penalty, and that there is a positive association between the amount of weekly television viewing and this gross misperception of the Austrian justice system.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, TV may bring about source confusion, i.e., heavy TV viewers may confuse fact for fiction and fiction for fact (Mares, 1996). In line with cultivation theory, Till et al (2016) summarized previous studies in the field of media psychology, citing evidence for biased judgments about real-world events as a result of TV consumption. However, they noted that research so far has only focused on biased judgments and expectations about the real world (so-called first-order effects) and the resulting behavior (so-called second-order effects) of television exposure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations